German operetta on Broadway and in the West End, 1900-1940 - Scott, Derek B. (Cambridge : Cambridge University Press, 2019)
Academic attention has focused on America's influence on European stage works, and yet dozens of operettas from Austria and Germany were produced on Broadway and in the West End, and their impact on the musical life of the early twentieth century is undeniable. In this ground breaking book, Derek B. Scott examines the cultural transfer of operetta from the German stage to Britain and the USA and offers a historical and critical survey of these operettas and their music. In the period 1900-1940, over sixty operettas were produced in the West End, and over seventy on Broadway. A study of these stage works is important for the light they shine on a variety of social topics of the period - from modernity and gender relations to new technology and new media - and these are investigated in the individual chapters. This book is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 28 Jun 2019).
Keywords: Operetta -- 20th century